REKONSTRUKSI NILAI KETELADANAN PANEMBAHAN BODHO SEBAGAI INSTRUMEN PENGUATAN KARAKTER IPS - Pungky Mareta Arianti (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
Social Studies learning has so far been theoretical and less than optimal in instilling character, while the flow of globalization has led to the erosion of noble values among the younger generation. On the other hand, the younger generation is also starting to lose connection with their local historical identity due to the phenomenon of generational amnesia. This study aims to reconstruct the exemplary values of the local figure Panembahan Bodho and formulate their potential as an instrument for character strengthening in Social Studies learning. The research employs a qualitative approach with a library research method. Data collection was conducted through the exploration of various primary and secondary literature sources, including theses, scientific journals, books, and historical documents related to Panembahan Bodho and the Nyadran tradition at Makam Sewu in Bantul, Yogyakarta. The data analysis technique uses content analysis with the Miles and Huberman model. The findings reveal three main results. First, the historical profile of Panembahan Bodho shows a figure as a student of Sunan Kalijaga who chose to dedicate himself to Islamic da'wah, with the nickname "Bodho" representing the values of humility and asceticism. Second, the exemplary values reconstructed include religious and humanistic values, simplicity and asceticism, servant leadership, mutual cooperation, and local wisdom. Third, these values have great potential to be integrated into Social Studies learning, covering aspects of local history, character education, strengthening social identity, and implementing the Pancasila Student Profile. This study concludes that the reconstruction of Panembahan Bodho's exemplary values contributes to enriching local wisdom-based Social Studies materials and serves as a strategy for strengthening students' character in the era of globalization. ABSTRAK Pembelajaran IPS selama ini masih bersifat teoretis dan kurang maksimal dalam penanaman karakter, sementara arus globalisasi telah menyebabkan lunturnya nilai-nilai luhur di kalangan generasi muda. Di sisi lain, generasi muda juga mulai kehilangan koneksi dengan identitas sejarah lokalnya akibat fenomena generational amnesia. Penelitian ini bertujuan untuk merekonstruksi nilai-nilai keteladanan tokoh lokal Panembahan Bodho serta merumuskan potensinya sebagai instrumen penguatan karakter dalam pembelajaran IPS. Penelitian menggunakan pendekatan kualitatif dengan metode studi kepustakaan (library research). Pengumpulan data dilakukan melalui penelusuran sumber literatur primer dan sekunder, termasuk skripsi, jurnal ilmiah, buku, dan dokumen sejarah terkait Panembahan Bodho serta tradisi Nyadran Makam Sewu di Bantul, Yogyakarta. Teknik analisis data menggunakan analisis isi (content analysis) dengan model Miles dan Huberman. Hasil penelitian menunjukkan tiga temuan utama. Pertama, profil historis Panembahan Bodho menunjukkan sosok murid Sunan Kalijaga yang memilih mengabdikan diri dalam dakwah Islam, dengan julukan "Bodho" yang merepresentasikan nilai kerendahan hati dan asketisme. Kedua, nilai-nilai keteladanan yang direkonstruksi meliputi nilai religiusitas dan humanisme, kesederhanaan dan asketisme, kepemimpinan pelayanan, gotong royong, serta kearifan lokal. Ketiga, nilai-nilai tersebut memiliki potensi besar untuk diintegrasikan ke dalam pembelajaran IPS, mencakup aspek sejarah lokal, pendidikan karakter, penguatan identitas sosial, dan implementasi Profil Pelajar Pancasila. Penelitian ini menyimpulkan bahwa rekonstruksi nilai keteladanan Panembahan Bodho berkontribusi bagi pengayaan materi IPS berbasis kearifan lokal serta menjadi strategi penguatan karakter peserta didik di era globalisasi.